Development, validity and reliability testing of the East Midlands Evaluation Tool (EMET) for measuring impacts on trainees' confidence and competence following end of life care training. Issue 4 (2nd February 2017) - Whittaker, B; Parry, R; Bird, L; Watson, S; Faull, C
Abstract : Objectives: To develop, test and validate a versatile questionnaire, the East Midlands Evaluation Tool (EMET), for measuring effects of end of life care training events on trainees' self-reported confidence and competence. Methods: A paper-based questionnaire was designed on the basis of the English Department of Health's core competences for end of life care, with sections for completion pretraining, immediately post-training and also for longer term follow-up. Preliminary versions were field tested at 55 training events delivered by 13 organisations to 1793 trainees working in diverse health and social care backgrounds. Iterative rounds of development aimed to maximise relevance to events and trainees. Internal consistency was assessed by calculating interitem correlations on questionnaire responses during field testing. Content validity was assessed via qualitative content analysis of (1) responses to questionnaires completed by field tester trainers and (2) field notes from a workshop with a separate cohort of experienced trainers. Test–retest reliability was assessed via repeat administration to a cohort of student nurses. Results: The EMET comprises 27 items with Likert-scaled responses supplemented with questions seeking free-text responses. It measures changes in self-assessed confidence and competence on 5 subscales: communication skills; assessment and care planning; symptom management; advance care planning; overarching values and knowledge. Test–retest reliability was found to be good, as was internal consistency: the questions successfully assess different aspects of the same underlying concept. Conclusions: The EMET provides a time-efficient, reliable and flexible means of evaluating effects of training on self-reported confidence and competence in the key elements of end of life care.